Respuesta :

1. Using the quadratic formula

[tex]x=(-b\pm\sqrt{b^{2}-4ac})/2a[/tex]

[tex]x=(-4\pm\sqrt{16-64} )/2[/tex]

[tex]x=[-4\pm(-4\sqrt{3}i)]/2\\x=-2\pm2\sqrt{3}i[/tex]

so, its c

-Hunter

Answer:

[tex]x = -2 \pm 2i\sqrt{3}}[/tex]

Explanation:

                      given quadratic sample: x²+4x+16=0

Quadratic formula: [tex]x = \frac{ -b \pm \sqrt{b^2 - 4ac}}{2a}[/tex]

Here a = 1, b = 4, c = 16         [ which are coefficients from ax²+bx+c ]

using the formula:

→ [tex]x = \frac{ -4 \pm \sqrt{4^2 - 4*1*16}}{2*1}[/tex]

→ [tex]x = \frac{ -4 \pm \sqrt{-48}}{2}[/tex]

→ [tex]x = \frac{ -4 \pm 4i\sqrt{3}}{2}[/tex]

→ [tex]x = -2 \pm 2i\sqrt{3}}[/tex]

ACCESS MORE